2013
DOI: 10.1021/ja4015277
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Strategy To Design Zeolite L Crystals with Tunable Morphology and Surface Architecture

Abstract: Tailoring the anisotropic growth rates of materials to achieve desired structural outcomes is a pervasive challenge in synthetic crystallization. Here we discuss a method to selectively control the growth of zeolite crystals, which are used extensively in a wide range of industrial applications. This facile method cooperatively tunes crystal properties, such as morphology and surface architecture, through the use of inexpensive, commercially available chemicals with specificity for binding to crystallographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 77 publications
8
136
0
Order By: Relevance
“…Often it is desirable to tune crystal size or introduce mesoporosity in Lewis acid zeolites to allow better diffusion to and from active sites and decrease the chance of pore blockage owing to deposition of side products. To this end, Rimer et al (30,31) have shown that zeolite growth modifiers are capable of modulating zeolite crystal structure. Ouyang et al (32) show that delaminated Sn-DZ-1, an MWW framework material with Sn postsynthetically incorporated into surface-accessible sites, has higher activity for the BV oxidation of 5-bromo-2-adamontanone with H 2 O 2 than Sn-Beta.…”
Section: Extended Propertiesmentioning
confidence: 99%
“…Often it is desirable to tune crystal size or introduce mesoporosity in Lewis acid zeolites to allow better diffusion to and from active sites and decrease the chance of pore blockage owing to deposition of side products. To this end, Rimer et al (30,31) have shown that zeolite growth modifiers are capable of modulating zeolite crystal structure. Ouyang et al (32) show that delaminated Sn-DZ-1, an MWW framework material with Sn postsynthetically incorporated into surface-accessible sites, has higher activity for the BV oxidation of 5-bromo-2-adamontanone with H 2 O 2 than Sn-Beta.…”
Section: Extended Propertiesmentioning
confidence: 99%
“…A suggested molecular sieve growth inhibitor 1,2,3-hexanetriol is deliberately selected to achieve crystallization process modification. The inhibitor was previously suggested by Rimer et al [50] to tailor the morphology of zeolite L for its strong interaction with zeolite surfaces. SAPO-34 with two different Si contents have been synthesized via the above proposed route, together with hydrothermally derived conventional ones for comparison.…”
Section: Crystallinity Textural Properties and Hierarchical Structurmentioning
confidence: 99%
“…9−11 It is important to emphasize that inhibitor−crystal interactions are not restricted to biological systems, but are also evident in synthetic crystallization. Notable examples include modifiers of organic crystals, 12,13 zeolites, 14,15 minerals, 16−19 and metal oxides. 20 In this study we focus on growth inhibition of calcium oxalate monohydrate (COM), which is the primary constituent of human kidney stones.…”
Section: ■ Introductionmentioning
confidence: 99%